Central America [in State of the Climate in 2015] - Amador Astúa, Jorge Alberto (2016)
The text discusses the analysis of weather stations in the region, including stations on both the Caribbean and Pacific slopes. Data from the NOAA/NCEI GHCN daily precipitation dataset for 2015 showed significant missing data and flagged values. To fill the gaps, historical precipitation records from national weather services were used, resulting in differences between the NWS data and the NOAA/NCEI dataset. These differences were as high as 420 mm and 560 mm for certain stations in 2015. The station climatology and anomalies were recalculated using the NWS data. Differences in precipitation totals were found between the NWS data and the NOAA/NCEI dataset, with the largest differences in David and Liberia.